2005
DOI: 10.1002/jmri.20243
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion and cervical invasion by endometrial carcinoma: Evaluation by CO2‐volumetric interpolated breathhold examination (VIBE)

Abstract: Purpose: To assess myometrial invasion and cervical invasion by endometrial carcinoma, using CO 2 -volumetric interpolated breathhold examination (VIBE) enabling more precise evaluation of depth of tumor invasion.Materials and Methods: CO 2 -VIBE was performed in 21 cases of endometrial carcinoma (Stage Ia-IIb) prior to treatment. The images were interpreted by performing multiplanar reconstruction (MPR), and the findings obtained from the images (degree of myometrial invasion and presence or absence of cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This capability improves the contrast resolution of the tumor and myometrium. In previ-ous studies [13][14][15], combining T2-weighted TSE with dynamic MRI improved staging accuracy from 61% to 90%. In our study, endometrial cancer was found to have high signal intensity on DWI; thus the boundary between cancer and normal myometrium was clearly depicted.…”
Section: Diffusion-weighted Mri Of Endometrial Cancermentioning
confidence: 95%
“…This capability improves the contrast resolution of the tumor and myometrium. In previ-ous studies [13][14][15], combining T2-weighted TSE with dynamic MRI improved staging accuracy from 61% to 90%. In our study, endometrial cancer was found to have high signal intensity on DWI; thus the boundary between cancer and normal myometrium was clearly depicted.…”
Section: Diffusion-weighted Mri Of Endometrial Cancermentioning
confidence: 95%
“…With the development of functional MRI imaging, diffusion weighted imaging (DWI) and dynamic contrastenhanced MRI (DCE-MRI) are increasingly applied to detect cervical infiltration in endometrial carcinoma [10][11][12][13][14]. Many studies have investigated the accuracy of MRI for detecting cervical invasion [6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These studies differ in the MR pulse sequences, magnetic field strength, and number of patients, so the results are diverse.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…With the development of functional imaging of MRI, diffusion weighted imaging (DWI) and dynamic contrast-enhanced MRI (DCE-MRI) are increasingly applied to detecting cervical infiltration in endometrial carcinoma [10][11][12][13][14]. A mass of studies have investigated the accuracy of MRI in detecting cervical invasion [6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These studies are different in MR pulse sequences, magnetic field strength, and number of patients, so that research results are diverse.…”
Section: Introductionmentioning
confidence: 99%